Optimizing Auxins Applications for In Vitro Plantlet Development of a New Dendrobium Hybrid - Etik Wukir Tini; Zulfa Ulinnuha; Rifqi Raditya Kurniawan; Pudji Widodo; Rendie Prasetyo; Abd. Rahman Milan; Gieks Sugiyono (Department of Agrotechnology, Universitas Muhammadiyah Yogyakarta, 2025)
This study investigated the effect of auxin types and concentrations on plantlet formation in the D. antennatum x D. stratiotes hybrid orchid during in vitro culture. This study was carried out experimentally using a Completely Randomized Split-Plot Design. The main plot was auxin types (IAA, IBA, and NAA), and the sub-plot was auxin concentrations (0, 5, 10, and 15 µM). Each treatment combination was repeated three times, resulting in 36 experimental units. The variable observed was plantlet formation, with the parameters measured including the number of shoots, shoot length, number of leaves, roots, and root length. The data obtained were analyzed using Analysis of Variance at 95% and 99% significance levels, followed by the Duncan Multiple Range Test (DMRT) at a 95% significance level. The results showed that D. antennatum x D. stratiotes hybrid shoots grown on MS medium supplemented with 15 µM auxin produced the highest number of shoots (13.66 shoots/explant) and leaves (32.11 leaves/explant). IBA application produced the longest shoots (1.67 cm/shoot), whilst NAA was more effective for root induction. MS media supplemented with 5 µM NAA resulted in the highest number of roots (36.33 roots/explant).